Effectiveness of Schema Therapy on Marital Relationship Quality and Emotion Regulation in Couples Affected by Infidelity - Pasha, Donya; Hatamipour, Khadijeh; Rostam Nezhad, Maryam (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Marital infidelity is the primary reason couples seek divorce, leading them to family counseling clinics. The current study aimed to investigate the effectiveness of schema therapy on marital relationship quality and emotion regulation in couples affected by infidelity. Methods and Materials: This was a quasi-experimental study with a pre-test-post-test control group design. The population included all couples in Nowshahr affected by infidelity in 2023. The sample consisted of 30 couples affected by infidelity (15 for the control group and 15 for the experimental group), selected through convenience sampling and randomly assigned to two groups. Data collection tools were the Busby et al. (1995) Marital Relationship Quality Questionnaire and the Garnefski and Kraaij (2006) Emotion Regulation Questionnaire. For data analysis, mean, standard deviation were used in the descriptive section, and multivariate analysis of covariance (MANCOVA) and SPSS version 26 were employed in the inferential section. Findings: The results showed that schema therapy had a significant effect on marital relationship quality (F = 72.99, P < 0.01) and emotion regulation (F = 51.44, P < 0.01) in couples affected by infidelity. Conclusion: It can be concluded that schema therapy was effective in improving marital relationship quality and emotion regulation in couples affected by infidelity, and can be utilized to reduce psychological problems in such couples.